Studies on cowpea varietal resistance to the cowpea flower and pod borer, Maruca Testulalis (Geyer) (Lepidoptera: Pyralidae) - Echendu, Thank-God Nnamdi (Obafemi Awolowo University, Ile Ife, Nigeria, 2023)
129p